Assessment of the Quality of Leadership in the Government of Technologies and Information Systems - Merchán, Vicente; Rodríguez, Rocío (Enfoque UTE, 2017)
Nowadays, leadership and the style of governing have become one of the quality criteria that challenges the Government of Technologies and Information Systems (GoTIS) value-based on public domain. In this aspect, the excellence models and GoTIS standards play a vital role in the success of the organizations due to their usefulness as systems that help the improvement towards the organizational excellence. Two of them are the Ibero-american Model of Excellence in Public Administration and the GoTIS standard ISO/IEC 38500. This paper takes them into account to create a new assessment model of GoTSI, the same one that is validated through the opinion of leaders of technologies and information systems of high-level. The work provides two sub-criteria, eleven dimensions and five components of assessment. This model will allow GoTIS assess itself as a principle of quality and, from there, make an improvement and an organizational change of the processes and GoTIS team decisions. Similarly, it will also help to open the way to the development of new quality criteria from a specific and comprehensive view.